Strategies of Perturbing Ion Homeostasis for Cancer Therapy. Issue 2 (5th January 2022) - Lee, DaeYong; Ha, JongHoon; Kang, Minjeong; Yang, Zhaogang; Jiang, Wen; Kim, Betty Y. S.
Abstract: Perturbing ion homeostasis has emerged as a novel therapeutic strategy for enhanced cancer therapy. Intensive development of ion homeostasis‐disturbing agents has been investigated to activate cell death signaling pathways in cancer or to boost antitumor immunity in immune cells. These approaches can treat cancer via new mechanistic behaviors. Although the anticancer mechanism of ion homeostasis‐disturbing agents is not yet clearly understood, a number of studies have recently been reported that demonstrate new possible mechanisms and their clinical applicability as novel anticancer agents. In this review paper, the authors elucidate various mechanisms for promoting cell death or activating antitumor immunity that are elicited using various ion homeostasis‐perturbing agents. Moreover, the authors provide a perspective of the future that makes a bridge between ion homeostasis and cancer immunotherapy for future innovation. Abstract : Perturbing ion homeostasis can induce programmed cell death, immune activation, or tumor microenvironments in a different way. This review highlights how ion homeostasis‐disturbing agents or materials triggered apoptosis/ferroptosis in cancer cells, activated innate or adaptive immunity, and influenced on angiogenesis and extracellular matrix formation. Also, the future directions of perturbing ion homeostasis for cancer therapy are discussed.